2017
DOI: 10.2478/prilozi-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rectus Sheath Block as a Supplement of General Anesthesia on Postoperative Analgesia in Adult Patient Undergoing Umbilical Hernia Repair

Abstract: The ultrasound guided rectus sheath block used for umbilical hernia repair could reduce postoperative pain scores and the amount of morphine consumption in 24 hours postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The analgesic efficacy of RSB in the case of umbilical hernia had been studied by Kartalov et al [15] . They evaluated the analgesic effects of the bilateral ultrasound guided RSB as supplement of general anesthesia on 60 patients undergoing elective umbilical hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic efficacy of RSB in the case of umbilical hernia had been studied by Kartalov et al [15] . They evaluated the analgesic effects of the bilateral ultrasound guided RSB as supplement of general anesthesia on 60 patients undergoing elective umbilical hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of local anaesthetic agents with a prolonged duration of action has led a revival of interest in this facet of local anaesthesia. 12 Previous authors have performed RSB for postoperative analgesia in various surgeries like major abdominal surgeries, [13][14][15] gynecological surgeries, 16,17 laproscopic surgeries 18 using different local anaesthetics (bupivacaine, 19 ropivacaine, 18 levobupivacaine, 13 ) and found promising results.…”
Section: Discussionmentioning
confidence: 99%
“…• Rectus Sheath Block: It is an anterior abdominal block that reduces postoperative pain associated with midline incisions around the umbilicus and laparoscopic surgery. Ultrasound-guided rectus sheath block will block the ventral rami of 7th-12th thoracolumbar nerve by injecting the LA into the space between the rectus muscle and posterior sheath [59]. Potential complications are related to LA toxicity and needle injury, namely injury to epigastric vessels and wound infections.…”
Section: Blocks Of Anterior Abdominal Wallmentioning
confidence: 99%
“…Potential complications are related to LA toxicity and needle injury, namely injury to epigastric vessels and wound infections. These are rare with ultrasound-guided blocks [59]. A study showed that rectus sheath block provided analgesia equivalent to epidural analgesia in colorectal surgery with advantage of lesser incidence of hypotension [60].…”
Section: Blocks Of Anterior Abdominal Wallmentioning
confidence: 99%